Radiokooistofdatering en teoiogiese refleksie - Botha, Pieter J. J. (HTS teologiese studies, 2001)
Radio-carbon dating and theological reflection. A brief description of radio-carbon and its implications serves as the context for a plea to extensively and radically revise "orthodox" Reformed theological discourse as practised in South Africa. Faith within a worldview determined by the atomic hypothesis is briefly explored by emphasising God-talk as moral discourse.